In situ stabilization of Cu+ for CO2 Electroreduction via Environmental-molecules-induced ZnO1-x shield - Fanxing Zhang; Ning Cao; Chentao Wang; Shengxiang Wang; Yi He; Yao Shi; Mi Yan; Ying Bao; Zhenglong Li; Pengfei Xie (Nature Communications)
Abstract Electrochemical CO2-to-ethanol conversion is challenged by sluggish C-C coupling kinetics and wide products distribution. Although Cu+ has been demonstrated to enhance multi-carbon (C2+) formation, the stabilization of Cu+ under reduction conditions is difficult. Here, we report a hydrogen-ethanol pretreatment strategy to obtain Cu nanoparticles covered by highly dispersed and disordered ZnO1-x clusters. Ethanol-induced ZnO1-x redispersion gives rise to abundant Cu+ on the subsurface. The optimal catalyst delivers a 73.0% ethanol Faradaic efficiency (FE) and 86.0% total C2+ FE at −0.9 V, with a 2.3 mmol cm−2 h−1 ethanol formation rate and single-pass ethanol yield of 18.0%. The catalyst also exhibits stability beyond 500 h, attributed to the stabilization of Cu+ by the ZnO1-x shield that requires a high energy barrier for lattice oxygen removal. In situ X-ray spectroscopy and calculations reveal a volcano relationship between Cu+ ratio in Cu species and ethanol FE. Optimal Cu+ density not only facilitates *OC-COH coupling but also optimizes the adsorption energy of *CH2CH2O on catalyst for ethanol electrosynthesis.